Designing Scenarios for Integrated and Sustainable E-Waste Management: Case of Indonesia - Alma Kenanga Attazahri; Utomo Sarjono Putro; Arfenia Nita (Indonesian Journal of Sustainability Accounting and Management, 2021)
Poorly managed e-waste can lead to public health and environmental problems resulting from the leakage of toxic e-waste substances. Building upon the integrated e-waste management (IEWM) concept, this study aims to propose an integrated and sustainable e-waste management strategy. It also suggests alternative processes for the effective collection, treatment, and disposal of e-waste. In its first stage of system dynamics modeling, the study employed an integrated approach comprising interviews and the Causal Loop Diagram (CLD). Based on the stakeholders’ collaboration and resource management, two alternative scenarios have been proposed: 1) integration to community collection; and 2) scavengers as collection agents. Both scenarios have been implemented by means of public–private partnership (PPP) with industries. Interrelating factors such as governance, physical system, and sustainability aspects have also been analyzed. The proposed alternative scenarios can benefit the municipal government in terms of improving the existing e-waste management channels and, therefore, facilitating a better e-waste management system. They can also ensure better collaboration with related stakeholders in recycling, manufacturing, smelter industry processes, etc., together with strengthening the relationship between the community and the informal sector.